2020
DOI: 10.1139/cjce-2019-0395
|View full text |Cite
|
Sign up to set email alerts
|

Application of nanotechnology in pavement engineering: a review

Abstract: Nanotechnology utilizes the research and technology established at the nuclear and molecular or macromolecular levels to comprehend the nanoscale phenomena. In road construction, the bituminous materials are used in enormous amounts. The macroscopic mechanical conduct of these materials still largely relies on microstructure and physical characteristics at a micro and nano scale level. For many years, scientists and engineers have been exploring nanotechnology in civil engineering, but nanotechnology use in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…The use of nanomaterials in asphalt revealed their potential to improve the pavement's mechanical and physical properties. [6][7][8][82][83][84][85] It has been shown that applying nanomaterials in the pavement industry can address the current shortcomings. Due to the lack of the operational requirements of the current pavement materials, safety, reliability, and mechanical performance are in high demand.…”
Section: Nano-modification Of Asphaltmentioning
confidence: 99%
“…The use of nanomaterials in asphalt revealed their potential to improve the pavement's mechanical and physical properties. [6][7][8][82][83][84][85] It has been shown that applying nanomaterials in the pavement industry can address the current shortcomings. Due to the lack of the operational requirements of the current pavement materials, safety, reliability, and mechanical performance are in high demand.…”
Section: Nano-modification Of Asphaltmentioning
confidence: 99%
“…As are those of nanometer size, making them promising additives for the reinforcement of materials with good performance in asphalt [5]. Modifications are essential to improve the efficiency of asphalt mixtures and, to some extent, solve problems of premature failure [6]. Therefore, the application of multidimensional nanomaterials in pavement engineering potentially improves asphalt mixtures, including adhesion between asphalt binder cohesions, cracking strengths, wetting strengths, rutting layer performances, and layer interface bonds [7].…”
Section: Introductionmentioning
confidence: 99%
“…3 Since recent years; several scientists 47 have paid more attention to the study of nanotechnology and its effect on improving the characteristics and quality of asphalt pavements. 8,9 Certain nanomaterials which are frequently used in asphalt improvement are nano clay, 10 carbon nanotubes, nano titanium dioxide, 11,12 nano zinc oxide, 13 carbon fibers. 14,15…”
Section: Introductionmentioning
confidence: 99%